"Moterų balsas" (Women’s voice) - the first newspaper for women in independent Lithuania - Čepytė, Julija; Garnienė, Živilė (Knygotyra, 1998)
Periodicals for women appeared only at the beginning of the 20th century. It was initiated by the national revival, more active women’s movement, the foundation of the first women’s organizations. The first newspaper for women in Lithuania was "Lietuvaitė" ("A Lithuanian girl"), first published in 1910 until 1914. The first newspaper for women in independent Lithuania was "Moterų balsas" ("Women’s Voice"), which was considered to continue "Lietuvaitė" tradition. The issue of both the papers was initiated by the Society of Lithuanian Women Catholics and the priest professor P. Januševičius. Both, the priest and the Society activists deserve a praise for the development of periodicals for women. "Moterų balsas", which was the paper of the Society of Lithuanian Women Catholics was published in Kaunas beginning with the second half of July 1918. There appeared six issues. The aim of the paper was to serve women’s needs, their education, and the defence of their rights, the needs of Lithuania, regarding the experience of women throughout the world. The editor of the paper was Z. Čalkytė (1898-1920), the most active coeditor was priest P. Januševičius. "Moterų balsas", which existed only half a year, was the basis for the further development of periodicals for women in Lithuania in 1918-1940. The new paper "Moteris" ("Women") was its sequel, published by the Society of Lithuanian Women Catholics in 1920-1940.